Immunization with Theileria parva parasites from buffaloes results in generation of cytotoxic T cells which recognize antigens common among cells infected with stocks of T. parva parva, T. parva bovis, and T. parva lawrencei - Kariuki, T.M.; Grootenhuis, J.G.; Dolan, T.T.; Bishop, Richard P.; Baldwin, Cynthia L. (1990)
Immunity to infection by the protozoan parasite Theileria parva in cattle is partially attributable to cytotoxic T cells, which kill lymphocytes infected with the schizont stage of the parasite. Here we evaluated five stocks of buffalo-derived T. parva lawrencei parasites and two stocks of cattle-derived T. parva parasites for their ability to induce in vivo cytotoxic T cells which can kill lymphocytes infected with a wide variety of strains of T. parva parasites. A group of seven full-sibling cattle, produced by embryo transfer and matched for at least one major histocompatibility complex class I haplotype, were immunized by infection and treatment with the parasite stocks. Target cells used in vitro cytotoxicity assays were infected with five buffalo-derived parasite stocks and five cattle-derived parasite stocks, including T. parva and T. parva bovis. Immunization with any of the seven parasite stocks resulted in the generation of cytotoxic T cells which recognized parasite antigens on most if not all of the target cell lines tested, although the T. parva bovis stock was the least effective at doing so. Further in-depth analyses performed with peripheral blood mononuclear cells from one of the cattle immunized with T. parva lawrencei parasites showed that the pattern of killing of the panel of target cells was altered when either cells infected with different parasite stocks or clones of infected cells were used as stimulator cells in vitro, suggesting the presence of more than one population of parasite-specific cytotoxic effector cells in the peripheral blood mononuclear cells. However, clones of these cytotoxic effector cells recognized common or cross-reactive antigen epitopes expressed by the entire panel of infected target cells. These T-cell clones will be useful for identifying common T-cell antigen epitopes of T. parva and the parasite genes encoding them.